PENGARUH INTRINSIC MOTIVATION DAN INNOVATIONCULTURE TERHADAP KNOWLEDGE TRANFER MAHASISWA DALAM PELAKSANAAN MAGANG - Harinurdin, Erwin (Jurnal Vokasi Indonesia, 2016)
There are two factors that encourage employees motivated in the work, which is intrinsic factor (motivator factors) and extrinsic (hygiene factors) (Herzberg, 1966) The purpose of this study was to determine whether the student intern intrinsic motivation has a positive effect on knowledge transfer, and for determine whether the innovative culture the organization has a positive effect on knowledge transfer student interns as well as to determine whether the innovative culture the organization has a positive influence on the intrinsic motivation of students internship. Berdasaskan test results using SEM known that intrinsic motivation is not proven to have influence postitif to transfer the knowledge and culture of innovation proven to have a positive influence on the transfer of knowledge and culture of innovation erbukti have a positive effect on intrinsic motivation